2014
DOI: 10.1007/s13187-014-0744-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of High eHealth Literacy in Primary Lung Cancer Survivors

Abstract: Lung cancer survivors are likely to have low health literacy which is an independent risk factor for poorer health outcomes. The eHealth literacy in lung cancer survivors has not been reported. The purposes of this study were to determine self-perceived eHealth literacy levels in lung cancer survivors and to explore predictors of higher eHealth literacy. A cross-sectional study was conducted at the Princess Margaret Cancer Centre in Toronto, Canada. Survivors completed a survey that collected demographic, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 22 publications
8
94
2
Order By: Relevance
“…14 Another study, however, evaluated e-health literacy among lung cancer survivors and found that they demonstrated low e-health literacy; higher e-health was correlated with the level of education and access to e-resources. 15 A survey of cancer survivors and cancer-free subjects found that health literacy and cancer-specific literacy were not greater among the survivors compared with those who were cancer free. 16 In this study the authors reported that there was an education effect and that higher literacy scores were correlated with a college education or greater compared with those with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study, however, evaluated e-health literacy among lung cancer survivors and found that they demonstrated low e-health literacy; higher e-health was correlated with the level of education and access to e-resources. 15 A survey of cancer survivors and cancer-free subjects found that health literacy and cancer-specific literacy were not greater among the survivors compared with those who were cancer free. 16 In this study the authors reported that there was an education effect and that higher literacy scores were correlated with a college education or greater compared with those with lower education levels.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the past several years, the eHEALS has been used for adults in a variety of study settings. 31,32 In our previous study with patients recruited from an ambulatory clinic (N = 69; mean age, 45.5 + 13.30) 33 the calculated alpha coefficient was .93. The patients who spent more time on the web demonstrated higher scores on the eHEALS ( r = .42, p = .03).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Although digital literacy is a relatively new concept in psycho-oncology, similar findings have begun to emerge in this area. For example, in a survey of lung cancer survivors, selfperceived digital literacy was generally low and inversely related to age (Milne et al, 2015).…”
mentioning
confidence: 99%